Adaptation to TV delays based on the user behavior towards a cheating-free second screen entertainment - Madeira, Rui Neves (2015)
Comunicação apresentada no ICEC, Isip International Conference on Entertainment Computing, 30 setembro a 2 de outubro 2015, Trondheim, Noruega